The Pluto files : the rise and fall of America's favorite planet - Tyson, Neil deGrasse (New York, NY : W.W. Norton, 2009)
"In August 2006, the International Astronomical Union voted Pluto out of planethood. Far from the sun, wonder Pluto has any fans. Yet during the mounting debate over rallied behind the extraterrestrial underdog. Disney created an irresistible pup by the same name, and, as one NASA scientist put it, Pluto was 'discovered by an American for America'. Pluto is entrenched in our cultural, patriotic view of the cosmos, and Neil deGrasse Tyson is on a quest to discover why. Only Tyson can tell this story: he was involved in the first exhibits to demote Pluto, and, consequently, Pluto lovers have freely shared their opinions with him, including endless hate mail from third graders. In his typically witty way, Tyson explores the history of planet recently been judged a dwarf." -- Publisher description.
Preface -- 1: Pluto in culture -- 2: Pluto in history -- 3: Pluto in science -- 4: Pluto's fall from grace -- 5: Pluto divides the nation -- 6: Pluto's judgment day -- 7: Pluto the dwarf planet -- 8; Pluto in the elementary school classroom -- 9: Plutologue -- Appendix A: Pluto data (2008) -- Appendix B: Planet X (complete lyrics by Christine Lavin) -- Appendix C: I'm your moon (complete lyrics by Jonathan Coulton) -- Appendix D: Pluto's not a planet anymore (complete lyrics by Jeff Mondak and Alex Stangl) -- Appendix E: Official media response from the author regarding the Rose Center's exhibit treatment of Pluto -- Appendix F: Resolution of the International Astronomical Union on the definition of a planet -- Appendix G: New Mexico Legislation relative to Pluto's planetary status -- Appendix H: California legislation relative to Pluto's planetary status -- Bibliography -- Acknowledgments -- Credits -- Index.
Includes bibliographical references (p. [181]-182) and index.
Keywords: Pluto (Dwarf planet); Astronomy; Pluto (Dwarf planet); Pluto (Dwarf planet); Astronomy; Pluto (Dwarf planet)